Obesity and overweight in South African primary school children -- the Health of the Nation Study. - Armstrong, M; Lambert, M; Sharwood, K; Lambert, E (2006)
OBJECTIVES: To determine the prevalence of overweight and obesity in a sample of South African children aged 6 - 13 years. DESIGN: Random sampling of schools within each provincial and socio-economic category. SETTING: Primary school children from 5 South African provinces. SUBJECTS: 10 195 (5 611 male and 4 584 female) primary school children. OUTCOME MEASURE: Height and weight were measured and body mass index (BMI) (weight (kg)/height (m) (2)) was calculated for each grouping (age x gender x ethnic group). Cut-off points for BMI defining obese and overweight for gender and age (6 - 13 years) were calculated in accordance with international standards. RESULTS: There were significant differences in height and mass between the different ethnic groups and genders. This trend was not evident for the BMI values. The prevalence of obesity within the sample was 3.2% for boys and 4.9% for girls, whereas overweight prevalence was 14.0% for boys and 17.9% for girls. When the contribution of each ethnic group was adjusted to the demographics of South Africa these values were only slightly different. The prevalence of obesity and overweight among boys was 2.4% and 10.9% respectively, while obese and overweight girls comprised 4.8% and 17.5%, respectively. CONCLUSIONS: South African children show trends of obesity and overweight, similar to values in developed countries about 10 years ago. Intervention strategies to combat an increasingly sedentary lifestyle may need to be developed for the South African context.